Vision-Mission Formulation in Early Childhood Education Institutions - Asyruni Multahada (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
The vision and mission is the most important point to direct an institution of early childhood education in to realize its objectives. Therefore, the formulation of vision and mission become the most important thing before organizing an institution of early childhood education. The formulation of vision and mission aims to realize a quality institution of early childhood education. The implementation of vision and mission can be done by formulating a strategic plan, and then socialized to stakeholders of early childhood education institution. All stakeholders of early childhood education institution, especially a headmaster, must have a strong commitment to work the vision and mission so that can be realized effectively and efficiently.